Effects of high and law constraint utterances on the production of immediate and delayed Echolalia in young children with Autism. - Rydell PJ; Mirenda P (Journal of Autism & Developmental Disorders, 1994)
This study examined the effects of adult antecedent utterances on the occurrence and use of echolalia in children with autism during a free play setting. Adult antecedent utterances were differentiated into two types, high and low constraint, based on the degree of linguistic constraint inherent in the adult utterance and social-communicative control exerted on the child's social and verbal interaction. Results of this study identified a variety of patterns of echolalia usage following adult high and low constraint utterances. Overall results found that a majority of immediate echoes followed high constraint utterances and were primarily used as responsives, organizational devices, and cognitives. The majority of delayed echoes followed low constraint utterances and were primarily used as requestives, assertives, and cognitives. Delayed echoes were more likely than immediate echoes to be produced with evidence of comprehension, but there were no differences in comprehension within the two categories of echolalia following high and low constraint utterances. Educational implications are discussed.